FEATURES OF RESTORATION OF DISPERSE POROUS MATERIALS - S. L. Rovin; L. E. Rovin; T. M. Zayats (Литьë и металлургия)
The article presents the results of research recycling of dispersed materials in rotary furnaces. Has been received new data on the of heat and mass transfer processes and carry out intensive and continuous process of solid- liquid-phase reduction of oxides in a single unit.